Etnomedisin Suku Dayak Kenyah Bakung Desa Umaq Bekuai Kecamatan Tabang Kabupaten Kutai Kartanegara Kalimantan Timur - Zuraida Sagala; Citra Listya; Merry Anggraeni (Journal of Tropical Ethnobiology, 2021)
Dayak Kenyah Bakung Ethnic that lives in Umaq Bekuai Village, Tabang, Kutai Kartanegara is one of Dayak Ethnic that stays in East Borneo. They have knowledge about using medicinal plant from generarion to generation. This experiment doing to get information about kinds of plant that used by Dayak Kenyah Bakung Ethnic people for healing, to know how to using the medicinal plant, in other side to inventory and identity kinds of medicinal plant based on the scientific name and their family. Sample in this experiment is the efficacy plants that used by Dayak Kenyah Bakung Ethnic and traditional medication. This experiment doing by interviewed of traditional heal and people, then collecting the efficacy plants by people in Dayak Kenyah Bakung Ethnic and be identified. The result of interview by a traditional healer and 14 Dayak Kenyah Bakung Ethnic folks it gets 30 kinds of plants that used as medicine, but only 26 that can be collected by researcher and four others cannot be collected because must through the certain rituals.